Murabahah contract in subsidized home ownership financing deed by notary in Bogor district - Erika Selorina; Frengki Hardian; Mohamad Ryan Bakry (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Akad Murabahah is a contract that finances an item by describing its purchase price to the buyer and asking the buyer to pay a higher price according to the agreed profit. The purpose of this research is to know and analyze the role of Notary in making a deed of financing subsidized home ownership and to know and analyze the murabaha contract in the deed of financing subsidized home ownership by notaries in Bogor Regency. This research uses normative legal research methods with the approach of legislation, norms, and doctrine as the main study, but is also supported by empirical approaches such as interviews to complement existing juridical data. The results of the study found that the role of notaries in making deeds of financing subsidized houses with murabaha contracts has not been widely carried out by Islamic banks, notaries in this case public officials who make deeds play more of a role in making ordinary commercial house financing. whereas when houses are subsidized, not many Islamic bank partners use notaries. Currently, the murabahah contract is still the choice of customers in buying houses at Islamic banks, because the margins offered by banks are not large and certain. However, there is a need for a kaffah concept of Islamic law in making deeds, for this reason this research is expected to conceptualize the anatomy of a murabahah contract based on applicable legal principles and Islamic legal values.